Extending the solid solution range of sodium ferric pyrophosphate: Off‐stoichiometric Na3Fe2.5(P2O7)2 as a novel cathode for sodium‐ion batteries - Pu, Xiangjun; Yang, Kunran; Pan, Zibing; Song, Chunhua; Lai, Yangyang; Li, Renjie; Xu, Zheng‐Long; Chen, Zhongxue; Cao, Yuliang (Carbon energy, 2024)
Iron‐based pyrophosphates are attractive cathodes for sodium‐ion batteries due to their large framework, cost‐effectiveness, and high energy density. However, the understanding of the crystal structure is scarce and only a limited candidates have been reported so far. In this work, we found for the first time that a continuous solid solution, Na4−αFe2+α/2(P2O7)2 (0 ≤ α ≤ 1, could be obtained by mutual substitution of cations at center‐symmetric Na3 and Na4 sites while keeping the crystal building blocks of anionic P2O7 unchanged. In particular, a novel off‐stoichiometric Na3Fe2.5(P2O7)2 is thus proposed, and its structure, energy storage mechanism, and electrochemical performance are extensively investigated to unveil the structure–function relationship. The as‐prepared off‐stoichiometric electrode delivers appealing performance with a reversible discharge capacity of 83 mAh g−1, a working voltage of 2.9 V (vs. Na+/Na), the retention of 89.2% of the initial capacity after 500 cycles, and enhanced rate capability of 51 mAh g−1 at a current density of 1600 mA g−1. This research shows that sodium ferric pyrophosphate could form extended solid solution composition and promising phase is concealed in the range of Na4−αFe2+α/2(P2O7)2, offering more chances for exploration of new cathode materials for the construction of high‐performance SIBs. Iron‐based pyrophosphate (Na4−αFe2+α/2(P2O7)2) is an attractive cathode for sodium‐ion batteries due to its cost‐effectiveness, feasible channels, and high operation voltage. Extending the solid solution range of Na4−αFe2+α/2(P2O7)2 enables generation of a novel off‐stoichiometric phase. Structural resolution, theoretical calculations, and sodium storage performance are comprehensively studied to disclose its structure–property relationship in sodium‐ion batteries.